Groundwater in the Na’ur area, Jordan: movement and pollution under changes in landscape uses - Alsawaeir, Dana; Abu-Jaber, Nizar; Lücke, Andreas; Mayr, Christoph; Lucke, Bernhard (Environmental Earth Sciences, 2024)
The Cretaceous karstified limestone aquifers in northwestern Jordan are the major source of water in the area. The study area lies to the south of Amman in a mostly rural area on the margin of the Jordan Valley Rift. Stable isotope and tritium data indicate that this is a recharge zone. Groundwater flows both towards the rift, where the springs emanate, and towards the east into the plateau region, possibly emanating in the Wadi Sirhan area in eastern Jordan. The geochemical analyses show that significant pollution is affecting the water in the more populated areas, while pollution in the agricultural areas occurs to a lesser extent. Thus, while the karst aquifers in the area receive recharge from a significantly larger catchment area, it is also vulnerable to pollution due to local mismanagement. Expanded urbanization not taking this into consideration will lead to increased groundwater degradation in the future.
CRIS-Team Scopus Importer:2024-05-10
Keywords: Geochemical; Isotopes; Pollution; Tritium